2020
DOI: 10.7249/rra134-3
|View full text |Cite
|
Sign up to set email alerts
|

The Digital Divide and COVID-19: Teachers' Perceptions of Inequities in Students' Internet Access and Participation in Remote Learning

Abstract: 4 At the time of the survey, 99.7 percent of teachers indicated that their schools had physically closed, with three-quarters of teachers reporting that their schools had closed by March 16, 2020.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 0 publications
2
45
0
3
Order By: Relevance
“…Consequently, the pandemic may widen the gap between the high-and low-income parents with respect to health and the ability to support their children. Second, low-income families are less likely than more affluent families to have high-quality internet service and computers in their homes, making it more difficult for their children to access online instruction (Stelitano et al, 2020). Third, relative to their more affluent peers, children from low-income families are more likely to attend public schools that lack the resources to support teachers' efforts to provide high-quality online instruction .…”
mentioning
confidence: 99%
“…Consequently, the pandemic may widen the gap between the high-and low-income parents with respect to health and the ability to support their children. Second, low-income families are less likely than more affluent families to have high-quality internet service and computers in their homes, making it more difficult for their children to access online instruction (Stelitano et al, 2020). Third, relative to their more affluent peers, children from low-income families are more likely to attend public schools that lack the resources to support teachers' efforts to provide high-quality online instruction .…”
mentioning
confidence: 99%
“…This is in accordance with Muximpua and Nhampossa (2020) recommendation that university students, during the COVID-19 new normal, need to be equipped with the devices, internet, and knowledge to navigate it. Stelitano et al (2020) findings also confirmed that many schools, primarily those with learners living in rural locations, have challenges accessing good internet facilities to respond to their studies during COVID-19 lockdown.…”
Section: Objective 1 Theme 3: Unpleasant Channels Of Teaching-learninmentioning
confidence: 55%
“…Recent literature in a high-income country such as the US has highlighted the gap in digital access during the COVID-19 pandemic. Teachers working in high-poverty schools were more likely to report that their students lacked internet access at home (Stelitano et al, 2020). With the multitude of challenges faced by school leaders in LICs and MICs, the NGO involved in this study was interested in exploring how the pandemic has impacted students learning remotely, and how they could better support their partner school leaders in addressing issues of equity.…”
Section: Theoretical Framework For the Studymentioning
confidence: 99%